STUDENT PERCEPTION OF UNIVERSITY SOCIAL RESPONSIBILITY IN A PUBLIC UNIVERSITY (Revista de Investigación Intercultural ASAMPITAKOYETE, 2025)
University Social Responsibility (USR) has become a strategic approach in the management of higher education institutions, aimed at integrating academic training, research, and community outreach for the benefit of sustainable development. This research aimed to analyze student perceptions of USR at a public university. The study was conducted using a quantitative, descriptive, cross-sectional, non-experimental design. The population consisted of 1,035 students, of whom 757 participated, selected through non-probability convenience sampling. The data collection technique was a survey, and the instrument was a structured questionnaire administered online. Descriptive and inferential statistics, including the Chi-square (χ²) test, were used to analyze the association between variables. The results show that most students perceive USR as an integrated management approach that integrates academic training, research, and community outreach. However, a significant gap was identified between conceptual knowledge of USR and effective participation in institutional activities, given that more than half of the students had not participated in USR projects. A favorable perception is observed regarding the connection between university social responsibility (USR) and formative research, as well as a high appreciation of the environmental approach and a strong willingness to participate in university volunteer programs. It is concluded that student perception of USR is mostly positive; however, challenges remain related to strengthening student participation, curricular integration, and the institutionalization of formative practices oriented toward social commitment, highlighting the need to consolidate USR as a cross-cutting axis of university management in public universities.
Keywords: University social responsibility; student perception; public university; social commitment; higher education